Bridging the BAME Attainment Gap: Student and Staff Perspectives on Tackling Academic Bias - Rana, Karan S.; Bashir, Amreen; Begum, Fatehma; Bartlett, Hannah (Frontiers in Education, 2022)
The Higher Education attainment gap between BAME students and their White peers is well documented. The cause of this gap is multifactorial, and there is a need to understand contributing factors to support the design of impactful interventions. The aim of this study was to probe student and staff understanding of what contributes to the attainment gap, and to collect feedback on how to reduce it. Qualitative data was collected from 110 STEM students (95% BAME and 75% female) and 20 staff (70% BAME and 80% female) from Universities in the West Midlands and London via one-to-one interviews and focus groups. Questions were developed across themes of support, inclusivity, and development. Transcripts were subjected to inductive and deductive thematic analysis. Key findings included: the need for cultural awareness and representation within student support services and pastoral care provision and tailored support for students who were first in their family to attend university. Students also felt the academic staff disproportionally represent their backgrounds, leading to a sense of not belonging amongst BAME students. BAME staff felt like tokens for diversity and reported having higher workloads than White staff, the social drinking culture felt isolating, participants felt that all staff should engage with cultural/ religious training and diversity of academic staff should be improved through inclusive recruitment practices and mentoring. The results highlight the need for access to academic and pastoral support that is culturally sensitive to all backgrounds.